PROBLEMATIKA HERMENEUTIKA SEBAGAI METODE TAFSIR AL-QUR’AN - Ahmad Shobiri Muslim (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Hermeneutics is one of the popular subjects in the world, especially in Indonesia. The subject of hermeneutics is taught in Islamic universities in Indonesia, particularly in the faculty of Ushuluddin. This paper will examine hermeneutics as a method of Qur’anic interpretation. It argues that hermeneutics is in fact based on negative assumptions about sacred texts, leading to the desacralization of the texts as well as the relativism of religious truth. This paper found that hermeneutics is relevant only as a method of biblical interpretation. There are problems when it is applied to the Qur’anic interpretation because Tafsir and Hermeneutics are two different methods.Keywords: Hermeneutika, Teks Suci, Tafsir